HUBUNGAN ASUPAN KARBOHIDRAT SEDERHANA DAN KECUKUPAN LEMAK DENGAN STATUS GIZI SISWA SDN TANJUNG - Hapsari, Sri; Dwi Handayani, Cindi; Annisa Ayuningtyas, RR; Sartono, Agus (Poltekkes Kemenkes Bengkulu, 2025)
In South Sumatra, the obesity rate in children reached 13.71% and tends to increase. It is suspected that this increase is related to consumption patterns, especially high intake of simple carbohydrates and adequate fat. This study aims to determine the relationship between simple carbohydrate intake and adequate fat with nutritional status. A cross-sectional study was conducted on 66 elementary school students, selected using the simple random sampling method. Student nutritional status data was measured using the BMI/U (Z-Score) indicator, simple carbohydrate intake and adequate fat data were measured using the SQ-FFQ method. The relationship test used the Spearman Rank test because all variable data were not normally distributed. The results showed an average simple carbohydrate intake of 75.05 ± 29.52 grams/day. Most (69.7%) children had a relatively high simple carbohydrate intake (>50 grams/day). The average fat adequacy was 131.50 ± 25.20% RDA, Most children (83.3%) were in excessive fat adequacy (>110% RDA). The average z score of BMI/A of children was 0.362 ± 1.639 kg/m², 59.1% of children were malnourished with 7.6% of them being underweight and 51.5% being overweight/obese. There was a relationship between simple carbohydrate intake and nutritional status (p = 0.000, r = 0.587). There was a relationship between fat adequacy and nutritional status (p = 0.000, r = 0.808). Simple carbohydrate intake and fat adequacy were positively related to children's nutritional status. Keywords : Simple Carbohydrate Intake, Fat Adequacy, Nutritional Status